The Development of a Professional Competency Evaluation Model of Nursing Students (International Journal of Nursing Education, 2021)
Purpose: The purpose of this research was to develop a professional competency evaluation model ofnursing students.Method: It was conducted through a research and development process divided into 4 steps as follows.1)Studying and analyzing elements and indicators from documents, interviewing experts, focus group andsurveying opinions. 2) Drafting a model by 10 experts applying the multi–attribute consensus reaching. 3)Implementing among nursing students, classmates, and teachers. 4) Evaluating by participants engaged in theimplementation. The statistics for data analysis comprised mean, standard deviation, median, interquartilerange, the Mann–Whitney U test and the Kruskal-Wallis Test.Findings: The results of the research were as follows. 1) The core competency of nursing students consistedof 7 elements and the functional competency included 4 elements. 2) The model had a structure that theevaluation objectives, expected outcomes, indicators, criteria, evaluators, method, duration, and feedback.3) It had a discriminant validity and could distinguish different professional competencies of the nursingstudents.4) The model was at a high level for all its aspects; feasibility, appropriateness, accuracy, andusefulness.Conclusion: The model was to develop a professional competency of nursing students.
Keywords: Development, Evaluation Model, Professional Competency, Nursing Students